Peningkatan Potensi Ibu Rumah Tangga Peternak Sapi Perah dalam Membuat Yoghurt di Desa Cibiru Wetan, Kabupaten Bandung, Jawa Barat - Aiyi Asnawi; Widhya Aligita; Soni Muhsinin; Eki Pratidina; Iceu Mulyati; Ika Kana Trisnawati; Ellin Febrina; Fauzan Zein Muttaqin (Universitas Mathla'ul Anwar Banten, 2021)
INCREASING THE POTENTIAL OF DAIRY CATTLE HOUSEWIVES IN MAKING YOGHURT IN CIBIRU WETAN VILLAGE, BANDUNG REGENCY, WEST JAVA. Yogurt is the product of milk fermentation by Lactobacillus subspecies. The unique properties of yoghurt provided by its living bacteria and its nutrients have captured the interest of the community. The highest price of cow's milk in dairy farming centres of Cibiru Wetan Village, Kabupaten Bandung is purchased by the Milk Processing Industry (IPS) at around IDR 4,500 / litre. Therefore, the purpose of this community service activity was the utilization of fresh cow milk as yoghurt to increase the income of dairy cattle farmer. Yoghurt processing begins with the modification of the incoming milk composition. This process typically involves reducing the fat content and increasing the total solids in the milk by are Lactobacillus bulgaricus and Streptococcus thermophilus. The stages of this activity began from providing an understanding of milk and dairy products and training in making yoghurt from fresh cow milk. The critical point in this activity is how to transfer knowledge and skills in preparing the starter and sterile conditions of the cooking utensils. The results of the activity showed that community participation could improve the knowledge and ability of participants in the processing of fresh cow milk as yoghurt. In conclusion, this activity could be an alternative income for dairy cattle farmer.